Roles of small peptides encoded by non-coding RNAs in tumor invasion and migration - Liu, Jie; Chang, Xiyue; Manji, Laeeqa; Xu, Zhijie; Xiao, Wan’an (Frontiers in Pharmacology, 2024)
Non-coding RNAs (ncRNAs), which are usually considered not to encode proteins, are widely involved in important activities including signal transduction and cell proliferation. However, recent studies have shown that small peptides encoded by ncRNAs (SPENs) have important roles in the development of malignant tumors. Some SPENs participate in the regulation of skeleton reorganization, intercellular adhesion, signaling and other processes of tumor cells, with effects on the invasive and migratory abilities of the cells. Therefore, SPENs have potential applications as therapeutic targets and biomarkers of malignant tumors. Invasion and migration of malignant tumor cells are the main reasons for poor prognosis of cancer patients and represent the most challenging aspects of treatment of malignant tumors.Currently, the main treatments for tumors include surgery, radiotherapy, targeted drug therapy. Surgery, however, is reserved for early stages of cancer and carries risks and costs. Radiotherapy and targeted therapy have serious side effects. This review describes the mechanisms of SPENs and their roles in tumor invasion and migration, with the aim of providing new targets for tumor diagnosis and treatment.